Development of Digital Technology Based Learning to Enhance Students Strategic Management Competencies - Dwi Cahyono; Rohim Rohim; Ardivan Avandi; Chua Toh Hua (Technomedia Journal, 2026)
The advancement of digital technology has become a major driving force behind the transformation of higher education in Indonesia, particularly in developing students' strategic management competencies, where active engagement and critical thinking are essential. This study employed a quasi-experimental approach with a pretest–posttest design to evaluate the effectiveness of technology-enhanced learning that integrates a Learning Management System (LMS), strategic simulation, and gamification elements. The research instruments consisted of a strategic competency test based on business case studies, digital literacy and student engagement questionnaires, and classroom observation sheets. Quantitative data were analyzed using paired-sample t-tests and Pearson correlation analysis, while qualitative data were examined through student feedback. This study addresses a gap in the Indonesian higher education literature, which has predominantly focused on student motivation, satisfaction, or engagement without directly assessing measurable improvements in strategic management competencies. The findings reveal that the simultaneous integration of an LMS, digital simulations, and gamification significantly enhances students' abilities in business environment analysis, strategy formulation, decision-making, and performance evaluation, thereby providing a more practical and strategically oriented learning experience. The novelty of this study lies in proposing a systematic and integrated digital learning model that bridges theoretical concepts and practical application through interactive simulations and gamification. This research contributes academically by enriching the literature on digital higher education in Indonesia and offers practical implications for developing adaptive curricula and data-driven instructional designs that foster active student engagement in the digital era.